Integrated electrocatalytic synthesis of ammonium nitrate from dilute NO gas on metal organic frameworks-modified gas diffusion electrodes - Donglai Pan; Muthu Austeria P; Shinbi Lee; Ho-sub Bae; Fei He; Geun Ho Gu; Wonyong Choi (Nature Communications)
Abstract The electrocatalytic conversion of NO offers a promising technology for not only removing the air pollutant but also synthesizing valuable chemicals. We design an integrated-electrocatalysis cell featuring metal organic framework (MOF)-modified gas diffusion electrodes for simultaneous capture of NO and generation of NH4NO3 under low-concentration NO flow conditions. Using 2% NO gas, the modified cathode exhibits a higher NH4 + yield and Faradaic efficiency than an unmodified cathode. Notably, the modified cathode shows a twofold increase in NH4 + production with 20 ppm NO gas supply. Theoretical calculations predict favorable transfer of adsorbed NO from the adsorption layer to the catalyst layer, which is experimentally confirmed by enhanced NO mass transfer from gas to electrolyte across the modified electrode. The adsorption layer-modified anode also exhibits a higher NO3 − yield for NO electro-oxidation compared to the unmodified electrode under low NO concentration flow. Among various integrated-cell configurations, a single-chamber setup produces a higher NH4NO3 yield than a double-chamber setup. Furthermore, a higher NO utilization efficiency is obtained with a single-gasline operation mode, where the NO-containing gas flows sequentially from the cathode to the anode.